CBT for common trauma responses - Scott, Michael J. (SAGE, 2013)
This is the first book to show how to use cognitive behavioural therapy (CBT) with the full spectrum of post-traumatic responses; exploring how they affect and relate to one another. Focusing not only on co-morbidity with other anxiety disorders and depression, the book looks more widely at, for example, co-existing pain, substance abuse and head injury.--